Landmarks of the Knowledge and Trypanosoma cruzi Biology in the Wild Environment - Jansen, Ana Maria; Xavier, Samanta Cristina das Chagas; Roque, André Luiz R. (Frontiers in Cellular and Infection Microbiology, 2020)
Trypanosomatids are ancient parasitic eukaryotes that still maintain prokaryotic characteristics. Trypanosoma cruzi, a primarily wild mammal parasite, infected humans already long before European colonization of the Americas. T. cruzi heterogeneity remains an unsolved question, and until now, it has still not been possible to associate T. cruzi genotypes with any biological or epidemiological feature. One of the first biochemical attempts to cluster the T. cruzi subpopulations recognized three main subpopulations (zymodemes) that have been associated with the transmission cycles in the wild (Z1; Z3) and in the domestic environment (Z2). The description of wild mammal species harboring Z2 two decades later challenged this assemblage attempt. Currently, the genotypes of T. cruzi are assembled in seven discrete typing units (DTUs). The biology of T. cruzi still shows novelties such as the description of epimastigotes multiplying and differentiating to metacyclic trypomastigotes in the lumen of the scent glands of Didelphis spp. and the capacity of the true meiosis in parallel to clonal reproduction. The study of the transmission cycle among wild animals has broken paradigms and raised new questions: (i) the interaction of the T. cruzi DTUs with each of its mammalian host species displays peculiarities; (ii) the impact of mixed genotypes and species on the transmissibility of one or another species or on pathogenesis is still unknown; (iii) independent T. cruzi transmission cycles may occur in the same forest fragment; (iv) the capacity to act as a reservoir depends on the peculiarities of the host species and the parasite genotype; and (v) faunistic composition is a defining trait of the T. cruzi transmission cycle profile. The development of models of environmental variables that determine the spatial distribution of the elements that make up T. cruzi transmission by spatial analysis, followed by map algebra and networking, are the next steps towards interpreting and dealing with the new profile of Chagas disease with its many peculiarities. There is no way to solve this neglected disease once and for all if not through a multidisciplinary look that takes into account all kinds of human and animal activities in parallel to environmental variations.